An Analysis of Implicature Found In Whatsapp Status - Sucihati, Theresia Budi (Universitas PGRI Madiun, 2024)
The implicature found in WhatsApp status is the main topic of this study. The study aims to define implicature and determine its various forms as well as its predominant form and significance. This study used Yule's (1996) theory and a qualitative design as its research methodology. The researcher's personal contact's WhatsApp status served as the data source. Furthermore, the researcher turns into the primary tool for the study. According to the results, there are three different categories of implicature: conventional implicature (1 data), particularized conversational implicature (7 data), and generalized conversational implicature (7 data). Conversational implicature written by a woman is the most common sort of implicature discovered in WhatsApp status updates. There were 20% men and 80% women among the findings. The meaning of each implicature kind varies. Without prior knowledge, generalized conversational implicature can comprehend. In contrast to specificized conversational implicature, readers need to fully comprehend the context. The final meaning of conventional implicature is that it requires other words to convey the meaning.